Some factors affecting replanting of smallholder rubber in Sri Lanka - Herath P H M U (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p31)
An econometric study indicates that the moving average of the rubber prices has significant (p=.05) positive effect on replanting. The total area to be replanted annually has significant role in this regard. Profit variable indicates negative impact on replanting, which shows with higher profit, the rubber growers tends to rely more on existing plantations. However, the impact is not significant. Although the research level studies indicated that the yield potential of the newly bred clones is very high, the average yield performance of these new clones is very high, the average yield performance of these new clones at the smallholder level has no significant effect on replanting.
Keywords: Rubber; Smallholder; Sri Lanka